59.4k views
0 votes
O(d)'?
Which expression is equivalent to

O(d)'? Which expression is equivalent to-example-1

1 Answer

4 votes

Answer:

2nd Option:


\frac{1}{ {a}^(42) }

Explanation:


{( {r}^( - 7)) }^(6)

Since,


{( {a}^(x)) }^(y) = {a}^(xy)

Then,


= {r}^( (- 7 * 6)) = {r}^( - 42)

Since,


{a}^( - 1) = (1)/(a)

Then,


= {r}^( - 42) = \frac{1}{ {r}^(42) }

Therefore,

2nd Option is correct.

User Jryl
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.